Research on the impact of digital economy on rural consumption upgrading: evidence from China family panel studies - Zhou, Qiuyang (Technological and Economic Development of Economy, 2023)
This paper examines the digital economy’s impact on rural household consumption upgrading. Existing studies remain mainly at the level of rural consumption scale and rarely address the consumption structure. The specific impact of the development of the digital economy on rural consumption upgrading and its mechanisms of action deserves in-depth study and consideration. We analyzed the related content using the fixed-effect model, the instrumental variable method (IV), the mediation effect model, and three-year panel data from the China Family Panel Studies (CFPS). This study found that, at the scale level, the digital economy contributes to expanding rural household consumption. At the structural level, the digital economy significantly increases the share of enjoyment-oriented household consumption but has no significant effect on development-oriented consumption. Income is an important transmission mechanism for the digital economy to improve rural household consumption. Besides, the impact of the digital economy on the upgrading of rural consumption varies according to income level and age. First published online 23 August 2023